Workplace locations of allied health and nursing graduates who undertook a placement in the Northern Territory of Australia from 2016 to 2019: An observational cohort study. (7th September 2021) - Campbell, Narelle; Farthing, Annie; Lenthall, Sue; Moore, Leigh; Anderson, Jessie; Witt, Susan; Rissel, Chris
Abstract: Objective: The aim of the study is to determine the current work locations of allied health professionals and nurses who undertook a student placement in the Northern Territory of Australia from 2016‐2019. Design: An observational cohort study was conducted in October 2020, with students emailed a link to an on‐line survey, plus two reminders. Setting: Primary health care in the Northern Territory of Australia. Participants: All allied health and nursing students who undertook a student learning placement in the Northern Territory from 2016‐2019 (n = 1936). Main outcome measures: Practicing nurses and allied health professionals were asked about their work history and locations (coded using the Modified Monash Model of remoteness and population size). Results: The response rate was 14.2% (275/1936 students). Most respondents reported that their placement positively influenced them to consider working: in a rural or remote location (76%), in the Northern Territory (81%), and with marginalised or under‐served populations (74%). Of the respondents, 224 had graduated and 203 were currently working in their health profession. A total of 31.4% of respondents reported that they had worked in a remote or rural location after graduation. Conclusions: The student placement had a positive effect on the likelihood of students working in a rural or remote location. A focus on recruiting students with a remote upbringing/background and offering longer placements would likely be successful in helping build the health professional workforce in remote locations.